The Cichlidae fish Geophagus brasiliensis (Quoy & Gaimard, 1824) has suitability as a sentinel species for changes caused by xenobiotics? - Claudio Nona Morado; Magda Fernandes de Andrade-Tubino; Benjamin Carvalho Teixeira Pinto; Francisco Gerson Araujo (Acta Scientiarum: Biological Sciences, 2022)
Industrial wastewater and agricultural practices are among the main activities discharging organic pollutants, such as Polychlorinated biphenyl (PCB) congeners and organochlorine insecticides (e.g. DDT - dichloro diphenyl trichloroethane), to the environment. In this study, we used the native Cichlidae fish species Geophagus brasiliensis as a sentinel to evaluate the hepatic 7-ethoxyresorufin-O-deethylase EROD activity, a biomarker of exposure to CYP1A-inducing pollutants, to assess the bioavailability of xenobiotics in two reaches of a large lotic system in Southeast Brazil: a less disturbed area (site 1) in the upper stretch, and an area in the middle stretch, which receives various industrial and agricultural effluents from upstream cities (site 2). In addition, G. brasiliensis were exposed to a single dose of 50 mg kg-1 beta-naphthoflavone (BNF) or of 50 mg kg-1 dimethylbenzoanthracene (DMBA) to test the effects on, respectively, the hepatic EROD activity in S9 supernatant fraction, and the frequency of micronucleated erythrocytes three days after the i.p. treatments, and compared to an unexposed group, to test its potential as a sentinel for biomonitoring studies. The EROD activity was approximately two-fold higher in fish from the impacted stretches than in fish from the less disturbed stretches (p < 0.05). Micronuclei (MN) frequency was also significantly different (p < 0.01) in DMBA-treated fish. The induced EROD activity in the impacted site suggests that organochlorinated pollutants are reaching the biota of the Paraíba do Sul River, confirming the suitability of Geophagus brasiliensis as a useful sentinel species to detect changes caused by xenobiotics